Gestão de fatores de risco e de proteção psicossociais em empresas de tecnologia da informação - Rugeri, Sabrina (My University, 2023)
The world based on technological processes is moving exponentially, which has an impact on the overall health of workers in this context of digital transformation. This study aims to analyze the management processes of psychosocial risk and protective factors in Information Technology companies from the perceptions of managers in the People Management area. The investigation is based on two theoretical pillars: People Management in Information Technology companies and Psychosocial Factors at Work (risk and protection). The research has a qualitative, applied, transversal, exploratory, and descriptive approach. Data collection took place through semi-structured interviews in the first half of 2022, with managers from the People Management areas of five Information Technology companies located in Serra Gaúcha. The collected data were analyzed using Bardin's content analysis technique and qualitative research analysis software, Atlas. ti. The study made it possible to identify, based on the perceptions of managers in the People Management areas of Information Technology companies, the psychosocial risk and protection factors present in the work environment and their forms of management. The collected data made it possible to describe and systematize the management processes of psychosocial factors in the researched context and were useful to recognize indicators of maturity in the management of psychosocial risks and protection in Information Technology companies. Based on the results, a Psychosocial Factors Management Program divided into five stages was proposed, which will allow managers to be equipped for the strategic management of psychosocial risk and protection factors. The study also highlighted the mobilization capacity of managers to expand organizational support to work teams during the COVID-19 pandemic regarding the critical health care of its members. [resumo fornecido pelo autor]
O mundo firmado em processos tecnológicos está se movendo de forma exponencial, o que repercute na saúde integral dos trabalhadores nesse contexto de transformação digital. O presente estudo tem como objetivo analisar os processos de gestão de fatores de risco e de proteção psicossociais em empresas de Tecnologia da Informação a partir das percepções dos gestores da área de Gestão de Pessoas. A investigação está sustentada em dois pilares teóricos: Gestão de Pessoas em empresas de Tecnologia da Informação e Fatores Psicossociais no Trabalho (de risco e de proteção). A pesquisa caracteriza-se como de abordagem qualitativa, aplicada, transversal, exploratória e descritiva. A coleta de dados aconteceu por meio de entrevistas semiestruturadas no primeiro semestre de 2022, com gestores das áreas de Gestão de Pessoas de cinco empresas de Tecnologia da Informação localizadas na Serra Gaúcha. Os dados coletados foram analisados a partir da técnica de análise de conteúdo de Bardin e por meio da utilização de um software de análise qualitativa de pesquisa, o Atlas.ti. O estudo possibilitou identificar, a partir das percepções de gestores das áreas de Gestão de Pessoas de empresas de Tecnologia da Informação, os fatores psicossociais de riscos e de proteção presentes no ambiente de trabalho e suas formas de gerenciamento. Os dados coletados permitiram descrever e sistematizar os processos de gestão de fatores psicossociais no contexto pesquisado e foram úteis para reconhecer indicadores de maturidade na gestão de riscos e de proteção psicossociais em empresas de Tecnologia da Informação. A partir dos resultados foi proposto um Programa de Gestão de Fatores Psicossociais divididos em cinco etapas, o que permitirá instrumentalizar os gestores para a gestão estratégica de fatores psicossociais de riscos e de proteção. O estudo também destacou a capacidade de mobilização dos gestores para ampliar o suporte organizacional às equipes de trabalho durante a pandemia da COVID-19 quanto aos cuidados com a saúde integral de seus membros. [resumo fornecido pelo autor]
Keywords: Ambiente de trabalho -Aspectos psicológicos; Bem-estar social; Psicologia social; Trabalho -Aspectos psicológicos; Work environment - Psychological aspects; Public welfare; Social psychology; Work - Psychological aspects